Investigating the Development of Teachers’ TPACK and the Adoption of Digital Storytelling: A Case Study of Teaching English in Elementary School - Amelia, Pratiwi; Rukmini, Dwi; Mujiyanto, Januarius; Bharati, Dwi Anggani Linggar (Journal of Asia TEFL, 2021)
This research investigated how two English teachers integrated information and communication technology (ICT) into English lessons by adopting a digital storytelling approach to further the progress of digital literacy of young students aged 9–11 years through peer online collaboration, research, problem-solving, and creation of a digital text. The context of this study is an elementary school located in an urban area in Semarang, Central Java, Indonesia. To begin with, we would like to introduce context details of English education in Indonesian elementary schools. English has been taught in Indonesian elementary schools since 2006. However, most English teaching at the elementary school level is not related to the students’ daily lives (Widodo, 2016). Rather than involving students in meaningful (Lestariyana & Widodo, 2018) and challenging (Sulistyo et al., 2019) games or projects, more focus is paid to teaching grammar and vocabulary